2008
DOI: 10.1111/j.1460-9568.2008.06177.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress accelerates neural degeneration and exaggerates motor symptoms in a rat model of Parkinson's disease

Abstract: The causes of most cases of Parkinson's disease (PD) are still poorly understood. Here we show that chronic stress and elevated corticosterone levels exaggerate motor deficits and neurodegenerative events in a Parkinson's disease rat model. Animals were tested in skilled and non-skilled movement while being exposed to daily restraint stress or oral corticosterone treatment. Stress and corticosterone compromised normal motor function and exaggerated motor deficits caused by unilateral 6-hydroxydopamine lesion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
86
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 63 publications
12
86
1
Order By: Relevance
“…The stress- and CORT-induced motor deficits shown here confirm previous studies of diminished reaching success and movement scores [20,22,23]. Appropriate changes in plasma CORT and glucose also confirm the salience of the present manipulations.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The stress- and CORT-induced motor deficits shown here confirm previous studies of diminished reaching success and movement scores [20,22,23]. Appropriate changes in plasma CORT and glucose also confirm the salience of the present manipulations.…”
Section: Discussionsupporting
confidence: 77%
“…Indeed, systemic administration of CORT or stress disturbs skilled and non-skilled movement at both acute and long-term intervals [19,20]. Moreover, motor function seems to be equally impaired by treatment with either stress or CORT [20,21,22,23]. These observations also apply to studies of brain damage.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although animals may show gradual habituation to daily restraint in physiological measures, it nevertheless causes chronically diminished motor deficits [19,22,35]. Similar findings were made in the young animals that displayed a modest increase in circulating CORT levels after three days of restraint and return to baseline levels at chronic time points.…”
Section: Discussionsupporting
confidence: 70%
“…Several reports have suggested that the GC-GR responses might be crucially linked to PD pathogenesis. Thus, chronically high levels of GCs were shown to exacerbate motor deficits in 6-hydroxy-DA-treated rats (11). This experimental observation corroborates clinical data showing that stress can trigger or worsen motor symptoms in PD patients (12).…”
Section: And Refs Therein)supporting
confidence: 77%